Mesentericportal resection in the pancreatectomy for periampullary cancer - Rodríguez, Gustavo; Gatti, Adriana; Bruno, Gerardo; Balboa, Oscar (Cirugía del Uruguay, 2001)
Cephalic duodenopancreatectomy has pro ven to be the so/e treatment offering the possibility of cure vis-á-vis . periampular cancers. The results obtained within the last few years are encouraging, with mortality figures under 5%, e ven though there sti/1 exists a high morbility.